Fossil Invertebrate Taphonomy of the Devonian in the state of Paraná:: Contributions to the Studies on Hydrocarbon Potential Linked to the Folhelho Project (LAGESED-UFRJ) (Terr@ Plural, 2023)
Shales constitute a recent frontier of studies in Sedimentary Geology, stimulated by the newexploratory panorama of Shale Gas, despite being the sealant of many petroleum systems. However,in Brazil, the generation of natural gas associated with paleontological studies is unprecedented andfundamental for determining the real regional potentialities in a process of advancing scientific andtechnological knowledge. Taphonomic studies of fossil macrofauna and ichnology are integrated withsedimentological data, expanding the capacity for paleoenvironmental interpretation of the sedimentaryfacies. Samples from three distinct outcrops in the Campos Gerais region of the state of Paraná wereanalyzed and two tafofauna and three ichnofauna were identified: Skolithos, archetypical and distalCruziana. The paleontological analyses proposed here provide support for biostratigraphic correlations,paleoenvironmental and paleoecological interpretations of the outcrops prospected, assisting in theevaluation of the quality of the shales of the Ponta Grossa Formation from the point of view of hydrocarbon generation.